Association study of genetic variants of 17 diabetes‐related genes/loci and cardiovascular risk and diabetic nephropathy in the Chinese She population (中国畲族人群17个糖尿病相关基因位点的遗传变异与心血管风险和糖尿病肾病的相关性). (26th April 2013) - Chen, Gang; Xu, Yuan; Lin, Yinghua; Lai, Xiaolan; Yao, Jin; Huang, Baoying; Chen, Zichun; Huang, Huibin; Fu, Xianguo; Lin, Lixiang; Lai, Shenghan; Wen, Junping
Abstract: Background: Genetic determinations are important in type 2 diabetes (T2DM) pathology. We investigated associations between genetic variants of 17 diabetes‐related genes/loci, T2DM and diabetic complications in Chinese She subjects. Methods: A comprehensive gene‐based association study was conducted using 17 single nucleotide polymorphisms in Chinese She subjects with normal glucose tolerance ( n = 1119), impaired glucose regulation ( n = 1767), and T2DM ( n = 443). We applied major abnormal Minnesota Code findings to predict cardiovascular risk and estimated glomerular filtration rate to assess kidney function. Results: Nine variants in FTO rs8050136, WFS1 rs10010131, CDKN2A/B rs10811661, KCNJ11 rs5219, CDC123/CAMK1D rs12779790, JAZF1 rs864745, SLC30A8 rs13266634, CDKAL1 rs10946398, and HHEX/IDE rs5015480 were significantly associated with T2DM ( P < 0.05). Single nucleotide polymorphisms in WFS1 rs10010131, CDKN2A/B rs10811661, CDC123/CAMK1D rs12779790, JAZF1 rs864745, FTO rs8050136, and HHEX/IDE rs5015480 were associated with T2DM and impaired glucose regulation. Risk alleles in WFS1 rs10010131, IGF2BP2 rs4402960, CDKAL1 rs10946398, FTO rs8050136, KCNQ1 rs2237897, and ADAMTS9 rs4607103 were significantly associated with decreased homeostatic model assessment (HOMA)‐β ( P < 0.05). After adjusting for age, gender and body mass index, genetic variants JAZF1 rs864745, FTO rs8050136, and HHEX/IDE rs5015480 were significantly related to reduced estimated glomerular filtration rate ( P < 0.05). Genetic variants in WFS1 rs10010131, CDKN2A/B rs10811661, CDC123/CAMID rs12779790, JAZF1 rs864745, FTO rs80501360, CDKAL1 rs10946398, and HHEX/IDE rs5015480 correlated with abnormal major Minnesota Code findings ( P < 0.05). Conclusion: Variants in WFS1, CDKN2A/B, KCNJ11, CDC123/CAMK1D, JAZF1, SLC30A8, FTO, CDKAL1, and HHEX/IDE genes are significantly associated with T2DM in She Chinese subjects. JAZF1, FTO, CDKAL1, and HHEX/IDE are associated with diabetic nephropathy. WFS1, CDKN2A/B, CDC123/CAMK1D, JAZF1, FTO, CDKAL1, and HHEX/IDE are associated with cardiovascular risk.